Florística e fitossociologia em mata ciliar nativa e restaurada às margens do reservatório da Usina Hidrelétrica Salto Santiago, Estado do Paraná - Lima, Felipe Fiuza de (2017)
The purpose of this work was to evaluate the floristic and phytosociological structure of the permanent preservation area of the Salto Santiago Hydroelectric Power Plant reservoir, located at the lower course of Iguaçu river, southwest of Paraná State, comparing fragments of secondary forest in the middle stage of regeneration (remnant) with fragments restored with native species, in the transition between the the Seasonal Semideciduous and the Mixed Ombrofhylous Forest. 2,000 m² plots were installed in both typologies to evaluate the tree community above 10 cm of DBH (diameter at breast height), called stock 1, subplots of 100 m² to evaluate individuals smaller than 10 cm of DBH and with more of 3 meters high (stock 2) and still subplots of 10 m² to evaluate the natural regeneration counting individuals between 0.3 and 3 m high (stock 3). In all were sampled 1 hectare in the remaining area and 0.6 hectare in the restored area. The floristic and phytosociological survey showed that most of the species that occur in the permanent preservation area of the UHSS reservoir are naturally occurring in the two phytogeographic formations, Seasonal Semideciduous and the Mixed Ombrofhylous Forest, showing that the area is in a region of ecological or ecotone tension. However, in the direct comparison between exclusive species of each formation, the Seasonal Semideciduous forest has more representatives than the Mixed Ombrofhylous Forest. In all, 62 tree-shrub species belonging to 27 botanical families were found. The Fabaceae family was the most diverse in both communities. However, in relation to abundance, Sapindaceae was the most representative family, which in all stocks of the two communities, except in stock 1 of the restored area, was the family that had more representatives, especially the species Cupania Vernalis. Through the abundance matrix, it was found that there is similarity between the density of the regenerating strata between the communities, however in relation to the species composition, there are still differences between the communities. The species Cupania vernalis and Matayba elaeagnoides, presented a high capacity of natural regeneration in these places, being indicated for areas to be restored, mainly in densification works.